Replacing Palliative Care In Oncology With The Sustained Living Paradigm: Psychosocial Determinants And Lifelong Rehabilitation (The Review of Diabetic Studies, 2025)
Palliative care is now endorsed as an evidence-based component of high-quality oncology across the disease trajectory, yet the term still functions as a late-stage label in many health systems. This semantic burden is not a trivial branding problem: it can operate as a decisional cue that “active treatment has ended,” intensify fears of abandonment, and, in some contexts, fuel a harmful conflation with “passive euthanasia.” Such framing undermines early referral, weakens therapeutic alliance, and delays multidimensional support despite robust evidence that timely integration improves quality of life and reduces goal-discordant care [1-4].We propose the Sustained Living Paradigm (SLP) as a conceptual and operational alternative that preserves the clinical substance of palliative/supportive care while relocating its telos from “care at the end” to “continuity of living.” SLP is built on a triad of modifiable burdens—psychological distress, functional decline, and financial toxicity—translated into routine practice via measurable indicators, thresholds, and time-bounded response pathways. The framework specifies a continuity-oriented ethics audit (the Intention–Causality–Proportionality triad; NNO) and a systems-level failure signal (the Clinical Misdirection Hypothesis; KYYH) to make controversies surrounding treatment refusal empirically traceable rather than rhetorically escalated [5-6].Methodologically, this paper is a targeted narrative synthesis and implementation blueprint informed by clinical guidelines, randomized trials, and implementation science. We operationalize SLP as a four-layer continuity engine—Sensing (PRO/ePRO), Decision (triage thresholds), Action (tiered interventions), and Governance (learning health system feedback)—designed to be embedded in routine oncology workflows without extending visit length. SLP generates testable hypotheses and a pragmatic measurement set (IYS-G) to evaluate continuity, equity, and ethical robustness in real-world settings.